DETERMINATION OF OPTIMUM DESIGN PARAMETERS OF HORIZONTAL PARALLEL PIPE AND VERTICAL U-TUBE GROUND HEAT EXCHANGERS - Demir, Hakan; Koyun, Ahmet; Atayilmaz, S. Ozgur (AMER SOC MECHANICAL ENGINEERS, 2009)
The most important part of a ground source heat pump (GSHP) is the ground heat exchanger (GHE) that consists of pipes buried in the soil and is used for transferring heat between the soil and the heat exchanger of the ground source heat pump. Soil composition, thermal properties and water content affect the length of ground heat exchanger. Another parameter affects the size of the ground heat exchanger is the shape. There are two basic ground heat exchanger configurations: vertical U-tube and horizontal parallel pipe. There are plenty of works on ground source heat pumps and ground heat exchangers in the literature. Most of the works on ground heat exchangers are based on the heat transfer in the soil and temperature distribution around the coil. Some of the works for thermoeconomic optimization of thermal systems are based on thermodynamic cycles. This study covers comparative thermoeconomical analysis of horizontal parallel pipe and vertical utube ground heat exchangers. An objective function has been defined based on heating capacity, investment and energy consumption costs of ground heat exchanger. Investment and energy consumption costs were taken into account as total cost in the objective function. The effects of the soil thermal conductivity, number of pipes, thermal capacity of ground heat exchanger, pipe diameter and the burial depth on the objective function were examined. The main disadvantage of U-tube ground heat exchanger is higher borehole cost that makes installation cost higher than parallel pipe ground heat exchanger. To make reference functions equal for both type of ground heat exchangers, the borehole cost must be under 20 S/m (now 55 S/m) for a given heating or cooling capacity. The performance of ground heat exchangers depends on the soil characteristics especially the soil thermal conductivity.
Keywords: THERMOECONOMIC OPTIMIZATION; PUMP SYSTEM; BURIED PIPE; Engineering